Efficacy and safety of subcutaneous prophylaxis with dalcinonacog alfa in adults with haemophilia B. Issue 4 (6th May 2021) - Mahlangu, Johnny; Levy, Howard; Lee, Martin; Del Greco, Frank
Abstract: Aim: Phase 2b study to assess efficacy, safety, thrombogenicity, immunogenicity and tolerability with 28 days of daily dosing of subcutaneous (SQ) dalcinonacog alfa as prophylaxis for haemophilia B (HB). Methods: Adult males with a confirmed diagnosis of congenital HB (factor IX [FIX] activity <2%) received daily dalcinonacog alfa 100 IU/kg SQ until day 28. The primary efficacy endpoint was the number of participants who achieved a steady‐state FIX activity level ≥12%. Tolerability, thrombogenicity and immunogenicity were study safety endpoints. Results: Of 6 participants who received study drug, one discontinued the study on day 7 due to injection‐site reactions (ISR). Of the 5 participants completing the study, FIX activity level exceeded 12% in 3 participants at day 7, increasing to 4 participants on days 14, 21 and 28 and all 5 at day 29. Pharmacokinetic findings (including mean alpha and beta half‐life of 5.3 days and 3.9 days, respectively, and mean residence time of 6.2 days) supported prolonged effects. Thrombogenicity markers remained normal throughout prophylactic injections or showed some initial increases followed by decreases with continued dosing. Two participants had anti‐drug antibodies to dalcinonacog alfa at study end, none had neutralizing antibody. Two participants had ISR, both resolved. Reports of redness, swelling, tenderness or pain among the first 3 participants prompted dose‐splitting for the last 3 participants, leading to fewer ISR. Conclusion: Subcutaneous dalcinonacog alfa is effective in raising FIX levels into the mild haemophilia range, comparable to intravenous extended half‐life FIX clotting factors.